Drafting international contracts : an analysis of contract clauses - Fontaine, Marcel, docteur en droit (Transnational Publishers, 2006)
Features an analysis of the main clauses present in international contracts. This book offers an image or what the drafting of an international contract is or should be in the 21st century. It includes abundant quotations of actual clauses, with critical assessments. It helps understand how international contracts are drafted in practice.